2021
DOI: 10.1111/btp.13045
|View full text |Cite
|
Sign up to set email alerts
|

Lomami Buffer Zone (DRC): Forest composition, structure, and the sustainability of its use by local communities

Abstract: The recently created Lomami National Park has an extensive Buffer Zone where local communities are allowed to use forest products sustainably. However, the management of this Buffer Zone is hampered by inadequate understanding of the floristic composition and the impacts of harvesting certain plant products. To fill in this data gap, we established and sampled 30 vegetation plots of 40 × 40 m, and investigated the population structure of 11 useful tree species preferred by local communities.We found that the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Other studies reported that various uses that target particular stem sizes, affect SCDs differently as e.g. species used for firewood exhibit fewer stems in smaller size classes, whereas species used for construction are characterized by a lack of large stems (Batumike et al, 2022;Obiri et al, 2002). Our findings correspond to studies by Ajonina et al (2014a), who looked at mangroves of different degradation levels (as increasing intensity of wood extraction) in Cameroon, Gabon, RoC, and DRC.…”
Section: Effects Of Human-driven Degradation On Population Structuressupporting
confidence: 86%
See 1 more Smart Citation
“…Other studies reported that various uses that target particular stem sizes, affect SCDs differently as e.g. species used for firewood exhibit fewer stems in smaller size classes, whereas species used for construction are characterized by a lack of large stems (Batumike et al, 2022;Obiri et al, 2002). Our findings correspond to studies by Ajonina et al (2014a), who looked at mangroves of different degradation levels (as increasing intensity of wood extraction) in Cameroon, Gabon, RoC, and DRC.…”
Section: Effects Of Human-driven Degradation On Population Structuressupporting
confidence: 86%
“…A study in Gazi Bay in Kenya by Kihia (2014) reported changes in dominance and abundance of species when comparing disturbed and undisturbed sites. Additionally, population structures of species, the proportion of stems of different age or diameter classes, can provide knowledge about harvesting impacts and regeneration capacity as was demonstrated for different tropical forests including mangroves (Ajonina et al, 2014a;Batumike et al, 2022;Obiri et al, 2002). Other studies addressing mangrove degradation, either generally or specifically in Africa, often focused on loss of areal extent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Forests are a large repository of biodiversity, including non-timber forest products (NTFPs), on which riparian populations rely frequently [1][2][3]. One of these NTFPs' distinguishing features is their accessibility, even to people without cultivable land and/or sufficient income [4,5].…”
Section: Introductionmentioning
confidence: 99%